Abigail's Party - Leigh, Mike; Mutton, Dave; Steadman, Alison; Stern, Tim; Duvitski, Janine (Mike Leigh at the BBC, 2009)
TV production of the play by Mike Leigh. A study in social pretension. While Abigail throws her first teenage party two doors away, the grown-ups gather for their own quiet beano, but marital and social tensions build up. [ftvdb.bfi.org.uk]